Identifying and Treating Opioid Side Effects: The Development of Methylnaltrexone - Moss, Jonathan (Anesthesiology (Philadelphia), 2019)
Methylnaltrexone Reverses Chronic Opioid-induced Constipation: A Randomized, Controlled Trial. By Yuan CS, Foss JF, O'Connor M, Osinski J, Karrison T, Moss J, Roizen MF. JAMA 2000; 130:142-8. Reprinted with permission. Constipation is the most common chronic adverse effect of opioid pain medications in patients who require long-term opioid administration, such as patients with advanced cancer, but conventional measures for ameliorating constipation often are insufficient. To evaluate the efficacy of methylnaltrexone, the first peripheral opioid receptor antagonist, in treating chronic methadone-induced constipation. Double-blind, randomized, placebo-controlled trial conducted between May 1997 and December 1998. Clinical research center of a university hospital. Twenty-two subjects (9 men and 13 women; mean [SD] age, 43.2 [5.5] years) enrolled in a methadone maintenance program and having methadone-induced constipation. Laxation response, oral-cecal transit time, and central opioid withdrawal symptoms were compared between the 2 groups. The 11 subjects in the placebo group showed no laxation response, and all 11 subjects in the intervention group had laxation response after intravenous methylnaltrexone administration (P<.001). The oral-cecal transit times at baseline for subjects in the methylnaltrexone and placebo groups averaged 132.3 and 126.8 minutes, respectively. The average (SD) change in the methylnaltrexone-treated group was -77.7 (37.2) minutes, significantly greater than the average change in the placebo group (-1.4 [12.0] minutes; P<.001). No opioid withdrawal was observed in any subject, and no significant adverse effects were reported by the subjects during the study. Our data demonstrate that intravenous methylnaltrexone can induce laxation and reverse slowing of oral cecal-transit time in subjects taking high opioid dosages. Low-dosage methylnaltrexone may have clinical utility in managing opioid-induced constipation.